Differentiating early Parkinson's disease and multiple system atrophy with parkinsonism by saccade velocity profiles. Issue 12 (December 2019) - Terao, Yasuo; Tokushige, Shin-ichi; Inomata-Terada, Satomi; Fukuda, Hideki; Yugeta, Akihiro; Ugawa, Yoshikazu
Highlights: Patients with multiple system atrophy with parkinsonism (MSAP) showed low saccade peak velocity compared with normal subjects. The deceleration and acceleration periods of the velocity profile were prolonged in MSAP. Patients with Parkinson's disease showed normal acceleration and peak velocity but longer deceleration. Abstract: Objective: Patients with Parkinson's disease (PD) and multiple system atrophy both present predominantly with parkinsonism at early stages, whereas cerebellar symptoms are largely masked in multiple system atrophy with parkinsonism (MSAP). We sought to determine whether the velocity profiles of saccades could be used to differentiate between these two disorders, revealing the underlying basal ganglia and/or cerebellar dysfunction and brainstem pathology in these disorders. Methods: Sixteen MSA-P patients, 63 PD patients, and 36 age-matched normal subjects performed the visually guided (VGS) and memory-guided saccade (MGS) tasks. Targets were presented at eccentricities of 5, 10, 20, and 30 degrees. The amplitude, peak velocity, and duration of saccades were compared among subject groups. Duration was further subdivided into acceleration and deceleration periods, corresponding to the times before and after peak velocity. These parameters correlated with the severity of Parkinsonism as assessed by the UPDRS motor score. Results: Hypometria predominated in both PD and MSAP patients, whereas hypermetria, frequently noted in cerebellar ataxia, was rarely observed. Saccades in MSAP were characterized both by prolonged acceleration and deceleration periods with reduced peak velocity. In contrast, the velocity profile of PD patients was characterized mainly by the prolonged deceleration period. The changes observed in velocity profiles of MGS deteriorated with advancing severity of parkinsonism in MSAP and PD patients. Conclusion: Saccade profiles provide useful information for differentiating between PD and MSAP at early stages. While the changes in velocity profiles may be explained by the cerebellar and brainstem pathology in MSAP, the changes in velocity profile in both PD and MSAP correlated significantly with increasing severity of Parkinsonism in both disorders, suggesting a link with striatonigral pathology. Significance: The differential changes in saccade velocity profiles of MSAP and PD may be used as a measure indexing the progression of cerebellar and basal ganglia dysfunction as well as for assessing the functional improvement when clinical treatment becomes available.